Biochemical characterisation of a Kunitz-type inhibitor from Tamarindus indica L. seeds and its efficacy in reducing plasma leptin in an experimental model of obesity - Amanda Fernandes de Medeiros; Izael de Sousa Costa; Fabiana Maria Coimbra de Carvalho; Sumika Kiyota; Beatriz Blenda Pinheiro de Souza; Daniel Nogoceke Sifuentes; Raphael Paschoal Serquiz; Bruna Leal Lima Maciel; Adriana Ferreira Uchôa; Elizeu Antunes dos Santos; Ana Heloneida de Araújo Morais (Taylor & Francis Group, 2018)
A trypsin inhibitor isolated from tamarind seed (TTI) has satietogenic effects in animals, increasing the cholecystokinin (CCK) in eutrophy and reducing leptin in obesity. We purified TTI (pTTI), characterised, and observed its effect upon CCK and leptin in obese Wistar rats. By HPLC, and after amplification of resolution, two protein fractions were observed: Fr1 and Fr2, with average mass of [M + 14H]+ = 19,594,690 Da and [M + 13H]+ = 19,578,266 Da, respectively. The protein fractions showed 54 and 53 amino acid residues with the same sequence. pTTI presented resistance to temperature and pH variations; IC50 was 2.7 × 10−10 mol.L−1 and Ki was 2.9 × 10−11 mol.L−1. The 2-DE revealed spots with isoelectric points between pH 5 and 6, and one near pH 8. pTTI action on leptin decrease was confirmed. We conclude that pTTI is a Kunitz trypsin inhibitor with possible biotechnological health-related application.